2018
DOI: 10.1016/j.ijantimicag.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of triazole resistance in clinical Aspergillus fumigatus isolates in a specialist cardiothoracic centre

Abstract: In our specialist cardiothoracic centre, the prevalence of triazole-resistant A. fumigatus is alarmingly high (13.2%). The majority of azole-resistant isolates were from patients with CF. We found a higher prevalence of the environmentally driven mutation TR/L98H in our A. fumigatus isolates than in published UK data from other specialist respiratory centres, which may reflect differing patient populations managed at these institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 26 publications
1
39
0
2
Order By: Relevance
“…In Australia where the incidence of azole resistance is low (< 3%), 2/3 azole resistant isolates had the G54R mutation associated with high MICs to itraconazole and posaconazole (Talbot et al, 2018). A recent study from the United Kingdom employing the AsperGenius assay R (PathoNostics BV) showed that 16/22 (73%) isolates with the resistant phenotype harbored no mutations detected by this test (Abdolrasouli et al, 2018). The FungiplexR Aspergillus Azole-R IVD real-time PCR platform is also now available.…”
Section: Molecular Methods To Detect Azole Resistance In Aspergillus mentioning
confidence: 99%
“…In Australia where the incidence of azole resistance is low (< 3%), 2/3 azole resistant isolates had the G54R mutation associated with high MICs to itraconazole and posaconazole (Talbot et al, 2018). A recent study from the United Kingdom employing the AsperGenius assay R (PathoNostics BV) showed that 16/22 (73%) isolates with the resistant phenotype harbored no mutations detected by this test (Abdolrasouli et al, 2018). The FungiplexR Aspergillus Azole-R IVD real-time PCR platform is also now available.…”
Section: Molecular Methods To Detect Azole Resistance In Aspergillus mentioning
confidence: 99%
“…Studies have shown that AR Af isolates harbouring resistance-associated cyp51A variants are globally distributed, and are often found alongside wild-type A. fumigatus in a diverse set of environmental substrates, including: agricultural soil (13, 14), flower beds (13, 1517) and timber mills (18). Moreover, clinical cases of aspergillosis with AR Af isolates harbouring either TR 34 /L98H or TR 46 /Y121F/T289A continue to emerge (19, 20), with one study specifically linking a fatal case of aspergillosis to a genotypically indistinguishable isolate sourced from the patients own home (21). Retrospective studies of patients with invasive aspergillosis (IA) and infected with azole-resistant genotypes of A. fumigatus show an excess mortality of 25% at day 90 when compared against patients with wild-type-infections (22).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that ARAf isolates harboring resistance-associated cyp51A variants are globally distributed and are often found alongside wild-type (WT) A. fumigatus in a diverse set of environmental substrates, including agricultural soil (14,15), flower beds (14,(16)(17)(18), and timber mills (19). Moreover, clinical cases of aspergillosis with ARAf isolates harboring either TR 34 /L98H or TR 46 /Y121F/T289A continue to emerge (20,21), with one study specifically linking a fatal case of aspergillosis to a genotypically indistinguishable isolate sourced from the patient's own home (22). Retrospective studies of patients with invasive aspergillosis (IA) and infected with azole-resistant genotypes of A. fumigatus show an excess mortality of 25% at day 90 when compared with that of patients with wild-type infections, suggesting a growing clinical impact caused by the emergence of ARAf (23).…”
mentioning
confidence: 99%